Acute Poisoning and its Medicolegal Aspects in Patients Presenting at a Tertiary Care Hospital of Sindh (Medical Forum Monthly, 2024)
Objective: To assess acute poisoning and its medicolegal aspects in patients presenting at a tertiary care hospital of Sindh.Study Design: Observational StudyPlace and Duration of Study: This study was carried out at Liaquat University Hospital Jamshoro/Hyderabad from April 2014 to June 2015.Materials and Methods: 240 cases of acute poisoning were studied presenting at the outpatient departments and emergency wards of the Liaquat University Hospital Jamshoro/Hyderabad. Acute poisoning cases were selected according to inclusion and exclusion criteria. Tools used for gathering information were the; information obtained from attendants/relatives, history of patients him/herself, clinical presentation, clinical signs and symptoms, laboratory findings and moreover response to anti poisoning therapy. Data was analyzed on statix software 8.1 (USA). Data was analyzed using student`s t-test and Chi-square test for continuous and categorical variables respectively. P-value ≤0.05 was taken significant statistically.Results: Of 240 subjects, 147 (61.25%) were male and 93 (38.75%) were female. (p=0.01). Most of study subjects belong to low social class in present study. Mean age of subjects was 45±7.7 years. Male outnumbered to female as regards the acute poisoning (p=0.001). Acute poisoning for suicide purpose was noted in 54.1 % (n=130) of study subjects. Kacha sharab, organophosphate and diazepam were the most commonly used agents for poisoning purpose.Conclusion: Acute poisoning is increasing due to commonly available poisons such as drugs and pesticides. The public sector authorities should take measures for the proper implementation of handling of drugs, poisons and pesticides.